Avaliação da fotobiomodulação em modelo experimental de rinite alérgica induzida por ovoalbumina - Klein, Simone (2021)
Allergic rhinitis (AR) is an inflammatory disorder of the nasal mucosa and is a worldwide health problem with a significant impact on the quality of life. The main goal of AR treatment is to relieve symptoms. However, standard treatments have considerable side effects or are not effective. Photobiomodulation (PBM) has emerged as an alternative treatment. Here, we evaluated the effects of transcutaneous systemic (tail) or local (skin over nostrils) PBM using a light emitting-diode (LED). Adult rats were sensitized with 7 intradermal injections of ovalbumin (OVA) plus alum. After the immunization, a nasal challenge was performed by intranasal instillation of OVA (2%) daily for 7 days. The symptoms and signs of AR were then provoked by intranasal instillation of OVA (1%) daily for 3 days. The animals were treated with PBM (local or systemic) immediately after the last instillation of OVA. Our results showed that local PBM treatment (100mW power, 15J radiant energy, 5,35J/cm2 radiant exposure, 150 seconds, 3 consecutive days, 1 time/day) reduced mast cell degranulation in the nasopharynx and nostrils, levels of leukotriene B4, thromboxane A2, and interleukin 4 (IL-4) in the nasopharynx, as well as gene expression of IL-4. Moreover, we showed higher levels and gene expression of IL-10 after local PBM treatment. In conclusion, our data showed that local treatment with PBM improved parameters related to AR in an experimental model, and should be tested clinically.